“Friends” and “Game of thrones”: Comprehen- sion through Media Culture - Chandran, , Akhila (International Journal of Psychosocial Rehabilitation, 2020)
Spinning the wheel, the hand trips and drips on the quirk genre which sprinkles joy and mirth to the majority. With the transcending nature of mankind, the stream of entertainment brings forth variety and versatility. Interlacing cultural background with natural interest the ethical rules have backstabbed and commonality has taken root. Premieres, promos, previews, blockbuster hit its scene. People associate more with the character by tracing a distinct similarity with the story roots and the theme. To portray this concept, the paper analysis the two gigantean- “FRIENDS” and “GAME OF THRONES”. “FRIENDS” draws the carelessness and the realistic picture of bond and warmth which brings them together whereas, “GAME OF THRONES” pictures the war of fire and ice which fuses the diligent madness that drives them to embrace the Iron Throne. The chronic illness of pain and anger are full-fledged in one shot. Harbouring through this fictitious reality as an offspring of contemplation, people bravely bring about and mold the pattern. These patterns being social,cultural,ideas,beliefs,fashion. Adapting a situation and drawing its raw material have shaped man in and out. This prospective theory strikes a person. Favoring the circumstances society is raised to the hype of augmented surprises.